2022
DOI: 10.1097/gox.0000000000004134
|View full text |Cite
|
Sign up to set email alerts
|

Plastic Surgery Diversity through the Decade: Where We Stand and How We Can Improve

Abstract: Background: Several studies over the past decade have investigated diversity within the field of plastic surgery, yet it remains unclear if an increase has resulted. This study sought to review the status of diversity within plastic surgery over the last decade and form strategies for residency programs to increase diversity recruitment. Methods: Data analysis of racial demographics from the Association of American Medical Colleges databases was complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 24 publications
1
33
0
Order By: Relevance
“…Several studies have looked at racial and ethnic diversity among residency applications to plastic surgery programs and have found that Black and Hispanic applicants are severely underrepresented in plastic surgery residency programs despite many applying. 7,14,15 A few studies have also examined representation within academic plastic surgery by examining faculty composition, rank and research output, determining that women and minorities were underrepresented and had less research productivity. 9,16 These findings are consistent with the "leaky pipeline" phenomenon, where women and underrepresented minorities are not as highly represented in competitive specialties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have looked at racial and ethnic diversity among residency applications to plastic surgery programs and have found that Black and Hispanic applicants are severely underrepresented in plastic surgery residency programs despite many applying. 7,14,15 A few studies have also examined representation within academic plastic surgery by examining faculty composition, rank and research output, determining that women and minorities were underrepresented and had less research productivity. 9,16 These findings are consistent with the "leaky pipeline" phenomenon, where women and underrepresented minorities are not as highly represented in competitive specialties.…”
Section: Discussionmentioning
confidence: 99%
“…Although strides have been made in some medical specialties toward realizing this goal, plastic surgery has remained relatively stagnant over the last 40 years. 7,8 In a recent meta-analysis focusing on representation in faculty and leadership positions in plastic surgery, Chawla et al discuss the importance of mentorship and sponsorship for women and underrepresented minority students in plastic surgery. 9 The purpose of this study is to expand on these findings and discuss racial, ethnic, and sex diversity in the academic and professional realms.…”
Section: Introductionmentioning
confidence: 99%
“…A cademic plastic surgery continues to be a field overrepresented by men and those belonging to a Caucasian ethnicity. [1][2][3] Although women have constituted approximately 50% of medical school graduates over the last decade, less than 20% of academic plastic surgeon faculty and 10% of full professors or department chiefs are women. 1,[4][5][6][7][8][9] This has been described as the "leaky pipeline effect," in which there are fewer proportions of women as you move up the academic ladder.…”
mentioning
confidence: 99%
“…1,8 This phenomenon also applies to ethnicities underrepresented in medicine, facing similar difficulties in attrition and academic promotion in plastic surgery. 2,3,8,10 African Americans and Hispanic or Latino Americans each make up less than 5% of plastic surgery residents and faculty in the United States, with no significant increases in representation over the last decade. 3,10,11 Diversifying the field of academic plastic surgery can provide immeasurable benefits to a healthcare system with long-standing gender and racial disparities.…”
mentioning
confidence: 99%
See 1 more Smart Citation